TREATMENT TACTICS FOR ACUTE INTESTINAL INFECTIONS IN CHILDREN - Kodirov Khusanboy Solievich (Scholar Express Journals, 2024)
Acute intestinal infections occupy one of the leading places in the structure of infectious pathology in children. Their clinical manifestations include symptoms of intoxication (lethargy, decreased appetite, fever, etc.), syndromes of infectious toxicosis (toxicosis with exsicosis, neurotoxicosis, hypovolemic or infectious-toxic shock, etc.) and diarrheal syndrome. Often, intestinal infections can be severe and even lead to death. In this case, the duration of the disease and its outcome directly depend on the timeliness and adequacy of the prescribed therapy
Keywords: acute intestinal infections; etiopathogenesis; clinical diagnostic criteria